Trend level gene-gender interaction effect for the BDNF rs6265 variant on age of onset of psychosis. (October 2019) - Lodhi, Rohit J.; Wang, Yabing; Macintyre, Georgina; Crocker, Candice; Loverock, Alexandra; Henriques, Beatriz Carvalho; Heywood, Brodie; Sivapalan, Sudhakar; Bowker, Alexandra; Majeau, Brett; Bolt, Carol; Bugbee, Darren; et al.
Highlights: Male gender and age at regular cannabis use are associated with earlier age of onset of psychosis. We observed trend level gene-gender interaction effects for rs6265 on age of onset of psychosis, adjusting for age regular cannabis use. There was no main or interaction effect of rs2494732 on age of onset of psychosis. Abstract: A BDNF rs6265 [A/A] by gender by cannabis use interaction has been associated with age of onset of psychosis (AoP). We examined the gender and cannabis use-adjusted association between BDNF rs6265 [G>A] and AKT1 rs2494732 [T>C] and AoP. Data from 167 Caucasians on AoP and age at first regular cannabis use were collected. Kaplan-Meier and Cox regression analyses were conducted. A trend level gene-gender interaction effect was observed for the BDNF rs6265 A/A genotype, controlling for age at first regular cannabis use. Larger collaborative research projects are required to further investigate this effect.